Effects of phosphate glass on Cs+ immobilization in geopolymer glass-ceramics. Issue 4 (15th February 2023) - Liu, Qi; Feng, Liang; Sun, Yangshan; Fang, Shuqing; Zhang, Zhengyi; Han, Na; Wang, Jing; Zhang, Chong; Wang, Tianhe
Abstract: 137 Cs is a major element in radioactive waste of nuclear power plant and there have been numerous reports on immobilization of 137 Cs in the crystalline structure of pollucite (CsAlSi2 O6 ). In this work, Cs-polluted soil (metakaolin) and a specially formulated phosphate glass were sintered together to form a CsAlSi2 O6 -based glass-ceramic. Extensive experiments and characterizations by XRD, DSC, SEM, and EDS allowed optimum glass addition to be established. The formation temperature of CsAlSi2 O6 in the glass matrix was approximately 900 °C, significantly lower than those used in forming Cs-pollucite by conventional sintering methods. Raman spectroscopy and SEM studies confirmed that Cs + was immobilized in the crystalline structure of CsAlSi2 O6 and further, CsAlSi2 O6 crystals were encapsulated in the glass matrix. When the addition of phosphate glass was 10 wt%, the leaching rate was lowest (3.35 × 10-4 g m -2 d -1 ) and the bending strength was the highest (30 MPa). We believe that this study offers a potential alternative and some useful data for safe processing of radioactive waste at a relatively low temperature.